Miconia goldenbergiana (Melastomataceae, Miconieae): a new species from the Atlantic Forest, Brazil - Caddah, Mayara K.; Meirelles, Julia (Phytotaxa, 2018)
Miconia goldenbergiana, a new species from the Atlantic Forest in southeastern Brazil, is described and illustrated. The new species have been extensively collected since the end of the XIX century but have been confused with M. budlejoides and M. formosa, species that also have discolorous and suprabasal leaves and glomerulate inflorescences. From the first species, it can be distinguished by papyraceous leaves with the abaxial surface covered by lepidote trichomes. From the second species, it can be distinguished also by the texture of leaves, and by its narrower size, crenulate to serrulate margins and acute base, besides the smaller size of the flowers. The new species is known from the states of Espírito Santo, Rio de Janeiro and eastern São Paulo, and is in danger of extinction.